Targeted inhibition of BET proteins in HPV16-positive head and neck squamous cell carcinoma reveals heterogeneous transcriptional responses - Rao, Aakarsha; Stosic, Milan S.; Mohanty, Chitrasen; Suresh, Dhruthi; Wang, Albert R.; Lee, Denis L.; Nickel, Kwangok P.; Chandrashekar, Darshan S.; Kimple, Randall J.; Lambert, Paul F.; Kendziorski, Christina; Rounge, Trine B.; et al. (Frontiers in Oncology, 2024)
Human papillomaviruses (HPV), most commonly HPV16, are associated with a subset of head and neck squamous cell carcinoma (HNSCC) tumors, primarily oropharyngeal carcinomas, with integration of viral genomes into host chromosomes associated with worse survival outcomes. We analyzed TCGA data and found that HPV+ HNSCC expressed higher transcript levels of the bromodomain and extra terminal domain (BET) family of transcriptional coregulators. The role of BET protein-mediated transcription of viral-cellular genes in the viral-HNSCC genomes needs to be better understood. Using a combination of TAME-Seq, qRT-PCR, and immunoblot analyses, we show that BET inhibition downregulates E6 and E7 significantly, with heterogeneity in the downregulation of viral transcription across different HPV+ HNSCC cell lines. Chemical BET inhibition was phenocopied with the knockdown of BRD4, mirroring the downregulation of viral E6 and E7 expression. We found that BET inhibition directly downregulated c-Myc and E2F expression and induced CDKN1A (p21) expression, leading to a G1-cell cycle arrest with apoptotic activity. Overall, our studies demonstrate that BET inhibition regulates both E6 and E7 viral and key cellular cell cycle regulator E2F gene expression and cellular gene expression in HPV-associated HNSCC and highlight the potential of BET inhibitors as a therapeutic strategy for this disease while also underscoring the importance of considering the heterogeneity in cellular responses to BET inhibition.